Probability of Survival in Thoracic Trauma: Comparative Analysis of 100 Patients Attended in a Reference Hospital at Aracaju/SE - Gonçalves, Hélder; Rezende, Mateus; Urquieta, Isadora; Trindade, Leda M. D. F.; Cabral, Flávio L. D. (International Journal of Innovative Research in Medical Science, 2023)
Background: Trauma is an injury characterized by structural alterations or physiological imbalance, resulting from acute exposure to some form of energy. Annually, about 5.8 million people die from trauma in the world. In Brazil, around 484,917 people died from external causes in 2016. Among the types of trauma, thoracic trauma is an important cause of death, existing multiple pathologies and association with avoidable causes of death if there were adequate care. Trauma scores have been developed and revised over the years to predict the likelihood of survival for these patients and guide healthcare teams' strategies. Methods: observational, prospective, quantitative study of victims of thoracic trauma who were admitted to Hospital João Alves Filho in Sergipe, based on the collection of clinical and demographic data. Results: from the sample of 100 patients, the mean age was 39.32 years, with 85.0% being male. 53% were diagnosed with blunt trauma, of which 33% were victims of traffic accidents; 47% penetrating trauma, being 26% by cold weapons and 21% by firearms. The average survival of these patients was 93.2%. Concomitant lesions were observed in 62.0% of the cases, 45% in the extremities and 45% in the head and neck. Conclusion: the profile of trauma victims were men between 20 and 39 years old, due to blunt trauma caused by a car accident, with a high probability of survival and associated injuries in other body segments.